Russian-Turkmen Struggle Over Ashuradeh Island in the Caspian Sea in 19th Century - Furkan Külünk (Belleten)

(untitled)
From the 19th century onwards, Tsarist Russia began to dominate a wide area in Turkestan through economic and military incursions. While it carried out commercial activities in the coastal cities and peninsulas in the west and east of the Caspian Sea, it also went on to capture these regions, building military bases at strategic points. One place that the Russians considered of vital importance to capture was Ashuradeh Island. Located in the south of the Caspian Sea, this island, which facilitated access to Iran and Turkestan, was close to many trading ports, as well as being of crucial importance militarily. While the Russians were initially engaged in commercial activities there, they soon seized this region and turned it into a base. From 1838 onwards two distinct developments compounded Russian objectives in the area: on the one hand, conflicts between the Russian naval forces and the Yamut Turkmens, the indigenous people of the island; on the other, a diplomatic crisis between the Russian and Iranian governments. This study analyses the process of the occupation of Ashuradeh Island by Tsarist Russia, the conflicts between the Yamut Turkmens and Tsarist Russia from 1836 to 1873, the development of Russian influence on the island vis-à-vis Iran, and the general situation of the Turkmens during this period. Using British archival materials, personal notes of Russian soldiers and ambassadorial reports, this study evaluates the effects of the occupation of Ashuradeh Island, which served as an important base for Tsarist Russia’s military activities in Turkestan, on Russia, Iran, Britain and the Turkmens in the region.